Perbedaan Kelekatan Dewasa Ditinjau Dari Keterlibatan Ayah Pada Individu Emerging Adults - Yulastri Yulastri (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Father involvement is an important factor in an individual’s psychological development, including the formation of adult attachment patterns. Emerging adulthood is a transitional phase from adolescence to adulthood characterized by identity exploration, increasing independence, and the development of more intimate interpersonal relationships. Adult attachment patterns formed during this phase play a significant role in determining the quality of an individual’s future relationships. This study aims to examine differences in adult attachment based on father involvement among emerging adults. The study involved 298 respondents. Data were collected using the Father Involvement Scale and the Adult Attachment Scale. Data analysis was conducted using the Kruskal–Wallis test. The results showed significant differences in adult attachment based on father involvement, with a Kruskal–Wallis value of 47.016 and a significance level of p = 0.001. The highest mean rank was found in secure attachment, followed by preoccupied, dismissing, and fearful attachment. These findings highlight the importance of father involvement in fostering adaptive adult attachment patterns among emerging adults.